Urban–rural background disparities and their impact on college students' academic outcomes - Wang, Linchuan; Pang, Longlong; Yang, Sijia; Shui, Haiyue (Frontiers in Psychology, 2026)
BackgroundIn recent years, increasing attention has been devoted to the influence of urban–rural background disparities on students' educational outcomes. Focusing on undergraduate students with comparable performance on the National College Entrance Examination, this study examines whether urban–rural background disparities remain associated with academic outcomes in higher education in China.MethodsUsing data from 632 valid questionnaire responses, we construct a mediation model incorporating family economic conditions, parental educational attainment, and self-directed learning ability to explore potential associational pathways linking urban–rural background to academic outcomes.ResultsThe results show that, on average, students from urban backgrounds achieve significantly better academic outcomes than their rural counterparts. Further analyses indicate that urban–rural background is systematically associated with differences in family economic conditions, parental educational attainment, and self-directed learning ability, which are in turn statistically associated with academic outcomes and together account for a substantial portion of the observed disparities.ConclusionsBy embedding urban–rural background disparities into an analytical framework of college students' academic outcomes and jointly considering family-, individual-, and societal-level factors, this study extends the existing literature. Within the limits of a cross-sectional observational design, the findings clarify the associational structure linking family background, individual learning characteristics, and academic performance at the university level, and offer policy-relevant insights for improving learning conditions for rural students and promoting educational equity.